2013
DOI: 10.4236/nm.2013.44036
|View full text |Cite
|
Sign up to set email alerts
|

Neurorestorative Effects of Constraint-Induced Movement Therapy after Stroke: An Integrative Review

Abstract: Stroke has been considered as one of the main causes of death and of motor and cognitive sequels. Especially, many patients with upper limb hemiparesis improved their motor action and showed meaningful cortical changes after treatment with constraint-induced movement therapy. Therefore, this review aims to verify the literature about neuroimaging and behavioral evidences in the cortical reorganization through the use of the constraint-induced movement therapy. So, we conducted the literature research in indexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…These data determined that FL overuse enhances SVZ-derived cell migration to the peri-infarct motor cortex, survival, and differentiation in larger numbers compared with stroke alone. Behavioral overuse of an affected limb after stroke involves an increased excitability in the motor cortex adjacent to the stroke site (28). To directly test the role of cellular activity in neurogenesis after stroke, Designer Receptors Exclusively Activated by Designer Drugs (DREADD)-based chemogenetic tools were utilized.…”
Section: Resultsmentioning
confidence: 99%
“…These data determined that FL overuse enhances SVZ-derived cell migration to the peri-infarct motor cortex, survival, and differentiation in larger numbers compared with stroke alone. Behavioral overuse of an affected limb after stroke involves an increased excitability in the motor cortex adjacent to the stroke site (28). To directly test the role of cellular activity in neurogenesis after stroke, Designer Receptors Exclusively Activated by Designer Drugs (DREADD)-based chemogenetic tools were utilized.…”
Section: Resultsmentioning
confidence: 99%
“…[30] Aplicaciones en enfermedad cerebrovascular El proceso de instauración de esta modalidad terapéutica estará en dependencia de la aplicabilidad y generación de resultados a las personas sometidas al proceso; en ese sentido, Liepert encontró como resultado relevante un aumento del tamaño de la zona del abductor pollicis brevis, sugiriendo por un aumento de la excitabilidad de la red neuronal en el hemisferio lesionado de las personas con ECV crónica, [31] en áreas corticales como la corteza motora primaria, la corteza dorsal pre -motora y área motora suplementaria. [32] Universidad de Manizales -Facultad de Ciencias de la Salud del ECV. Entre los efectos significativos sobre función motora aportados se encuentra un meta -análisis, cuyas mediciones de la función motora del brazo mostró resultados positivos inmediatos, posterior a la aplicación del tratamiento en las personas con ECV, un efecto moderado sobre la actividad motora del brazo inmediatamente después del tratamiento, en 3-6 meses de seguimiento y una gran heterogeneidad entre los estudios en el ámbito de la actividad motora del brazo.…”
Section: Resultados Definición Y Reseña Históricaunclassified
“…Neuroimaging studies have shown that stroke patients participating in CIMT and mCIMT undergo neuroplastic changes in brain function and structure. Several cortical areas, such as the primary motor cortex, dorsal premotor cortex, and supplementary motor area, show increased electrical and metabolic neuronal activity during CIMT and mCIMT (Szaflarski, Page, Kissela, Lee, Levine, & Strakowski, 2006;Yadav, Sharma, Borah, & Kothari, 2016;Lucas et al, 2013).…”
Section: Discussionmentioning
confidence: 99%